Handbook of Population - Poston Jr., Dudley L. (Handbooks of Sociology and Social Research, 2019)
"Demography is a dynamic field that is constantly evolving, which is why the 2006 edition of The Handbook of Population was such a welcome update to earlier summation prepared in 1959 by Philip Hauser and Dudley Duncan. The second edition of The Handbook is likewise a welcome addition to the literature given the rapid pace of change in demographic research today. Not only have earlier updates on new topics such as biodemography and political demography been expanded, the new edition also contains entirely new chapters on emerging issues of demographic interest such as obesity, inequality, and adoption. Editor Dudley Poston continues to provide a great service to the field by keeping demographers abreast of the latest developments in population science." (Douglas S. Massey, Princeton, USA) "The 2nd edition of the Handbook of Population covers the major topics of the discipline of demography, including current substantive, methodological and theoretical issues of interest, as well as new and emerging topics in the field. In addition to revised, updated and extended chapters that were included in the 1st edition, this 2nd edition of the Handbook brings to the forefront entirely new chapters covering such major themes as children, adoption, sexuality, inequality, population psychology, rural demography, and obesity. Chapters in this Handbook will expand our knowledge of the field, and will raise awareness of the causes and the consequences of demographic behavior and events in societies throughout the world. This 2nd edition will also serve as a reference in the field of population studies for years to come. It will generate new questions and research ideas and will positively impact the growth, development, and expansion of demography.".